The impact of remittances on economic growth in Syria (Damascus University Journal for the economic and Political sciences, 2021)
Recently, remittances have increased dramatically in developing countries, and researchers are distinguished in their impact on economic growth, as two separate perspectives have emerged.  An optimistic view and a pessimistic one.  Optimists agree that remittances have a positive impact on the remittance recipient country by reducing poverty and stimulating economic growth.While the pessimists find that remittances do not stimulate economic growth, they are retarding the economy by excessively increasing consumption, Given these important ethics.This study was conducted in order to assess the effect of remittances on economic growth in Syria during the period 2000-2017 using the two-step Engel-Granger and Johansson model for estimating time series.  The study showed a short and long-term relationship between economic growth and remittances, as remittances contribute to a negative impact on economic growth, as well as investment in human capital. As for imports and government investment, the results showed a positive relationship in the short and long term.
Keywords: remittances; economic growth; error-correcting model, co-integration